2003
DOI: 10.1177/146442070321700406
|View full text |Cite
|
Sign up to set email alerts
|

Early-age finite element modelling of industrial ground floors

Abstract: A series of finite element (FE) models of ground floor slab behaviour has been developed and validated against in situ data from site instrumentations. Good agreement was obtained for thermal flow models, and the negative impact of air movement over the top of the slab has been highlighted. Plane stress models of slabs exposed to uniform and differential thermal gradients representing hydration and shrinkage effects demonstrated that the stresses resulting from frictional restraint are significantly less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The modelling work is reported in greater detail elsewhere. 5 Fig. 13 is included to show the agreement obtained between the model and the site-measured slab temperatures.…”
Section: Sample Resultsmentioning
confidence: 99%
“…The modelling work is reported in greater detail elsewhere. 5 Fig. 13 is included to show the agreement obtained between the model and the site-measured slab temperatures.…”
Section: Sample Resultsmentioning
confidence: 99%
“…The findings from the instrumentation of seven sites, discussing the influence of thermal and hygral effects on slab and joint movements, are presented elsewhere 3,4 as are the results of finite element modelling of the slab behaviour. 5 Further information on the research can also be found on the project website. 6…”
mentioning
confidence: 99%